Two new Horaiclavus (Horaiclavidae, Conoidea) species from the Indo-Pacific region - Bonfitto, Antonio; Morassi, Mauro (Zootaxa, 2014)
The genus Horaiclavus includes eight Holocene Indo-Pacific species (Appeltans et al. 2012). Herein, we describe two new species that resemble members of this genus in some aspects of shell morphology, but otherwise show features that suggest that they differ from “typical” Horaiclavus species. Descriptions and measurements were based on shells oriented spire up with the aperture facing the viewer and made using a Leica MS 5 Stereomicroscope for incident light and a 10× ocular micrometer. Scanning electron microscope (SEM) micrographs were taken using a Hitachi S-2400. The classification adopted here follows Bouchet et al. (2011). The following abbreviations are used in the text: MZB = Museo di Zoologia dell’Università di Bologna; MNHN = Muséum National d’Histoire Naturelle, Paris, France; NHMUK = The Natural History Museum of United Kingdom [formerly British Museum (Natural History)], London, United Kingdom; ZMA = Naturalis Biodiversity Center, Leiden, the Netherlands; ZRC = Zoological Reference Collection, Raffles Museum of Biodiversity Research, Singapore; a = aperture length; b = shell width; l = length; a/l = ratio of aperture length to total shell length; b/l = ratio of shell breadth to total length; dd= dead collected specimen(s); stn. = station.